On Studying Hierarchical Inter-Relationships amongst Barriers for Implementing Reverse Logistics in the Construction Sectors in India and Abroad - S. P. Singh; Remica Aggarwal (Contemporary Research in Business, Management and Economics Vol. 1, 2024)
Reverse logistics, defined by Reverse Logistics Executive Council as the process of moving goods from their typical final destination to another point, for the purpose of capturing value otherwise unavailable, or for the proper disposal of the products. Following research work explores the barriers and / or challenges in implementing reverse logistics in the construction sector. It afterwards, studied the hierarchical inter-relationships amongst them using ISM methodology.